2022
DOI: 10.1021/acs.analchem.2c01375
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Metabolic Profiling of Macrophages Using 3D OrbiSIMS: Correlations with Phenotype

Abstract: Macrophages are important immune cells that respond to environmental cues acquiring a range of activation statuses represented by pro-inflammatory (M1) and anti-inflammatory (M2) phenotypes at each end of their spectrum. Characterizing the metabolic signature (metabolic profiling) of different macrophage subsets is a powerful tool to understand the response of the human immune system to different stimuli. Here, the recently developed 3D OrbiSIMS instrument is applied to yield useful insight into the metabolome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Using a targeted approach to analyze the lipid palette (matching lipid ion peaks to LIPID MAPS database), it was found that M1 macrophages had the highest lipid counts and different lipid composition compared to M2 or M0. 38 The amino acid composition and other metabolites showed notable differences as well. Overall, the study represents a novel approach for in-situcharacterization of metabolic profiles to assess phenotypical differences between closely related cell types with single cell resolution.…”
Section: Single Cell Metabolomicsmentioning
confidence: 99%
“…Using a targeted approach to analyze the lipid palette (matching lipid ion peaks to LIPID MAPS database), it was found that M1 macrophages had the highest lipid counts and different lipid composition compared to M2 or M0. 38 The amino acid composition and other metabolites showed notable differences as well. Overall, the study represents a novel approach for in-situcharacterization of metabolic profiles to assess phenotypical differences between closely related cell types with single cell resolution.…”
Section: Single Cell Metabolomicsmentioning
confidence: 99%
“…Single-cell metabolomics technologies will reveal new insights into modulating metabolism with small molecules. 198 , 214 , 413 , 638 , 639 It can provide meaningful cell phenotype, enabling us to analyze cell status and obtain the overall biological information.…”
Section: Modulating Metabolismmentioning
confidence: 99%
“…They can adopt stimulus induced phenotypes because of their functional plasticity. This allows macrophages to appropriately respond to diverse pathogens and aid in tissue repair following acute damage [70]. M0 monocytes represent the common progenitor lineage for the pro-inflammatory M1 phenotype and the anti-inflammatory M2 phenotype.…”
Section: Single-cell Omicsmentioning
confidence: 99%
“…However, when coupled with the high mass resolving power and mass accuracy of an Orbitrap, characterizing metabolic profiles at the single-cell level is possible. Using a targeted approach to analyze the lipid palette (matching lipid ion peaks to the LIPID MAPS database), it was found that M1 macrophages had the highest lipid counts and dif-ferent lipid composition compared to M2 or M0 [70]. The amino acid composition and other metabolites showed notable differences as well.…”
Section: Single-cell Metabolomicsmentioning
confidence: 99%